Mechanism and management of diuretic resistance in congestive heart failure - Nag, Dipankar Chandra; Murshed, AKM; Chakrabortty, Rajashis; Rahman, Md Raziur (Journal of Dhaka National Medical College & Hospital, 2012)
Diuretic drugs are used almost universally in patients with congestive heart failure, most frequently the potent loop diuretics. Despite their unproven effect on survival, their indisputable efficacy in relieving congestive symptoms makes them first line therapy for most patients. In the treatment of more advanced stages of heart failure diuretics may fail to control salt and water retention despite the use of appropriate doses. Diuretic resistance may be caused by decreased renal function and reduced and delayed peak concentrations of loop diuretics in the tubular fluid, but it can also be observed in the absence of these pharmacokinetic abnormalities. When the effect of a short acting diuretic has worn off, postdiuretic salt retention will occur during the rest of the day. Chronic treatment with a loop diuretic results in compensatory hypertrophy of epithelial cells downstream from the thick ascending limb and consequently its diuretic effect will be blunted. Strategies to overcome diuretic resistance include restriction of sodium intake, changes in dose, changes in timing, and combination diuretic therapy. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12193 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 44-46